Insights into incompatible plasmids in multidrug-resistant Raoultella superbugs - Jiao Feng; Changxin Wu; Dongsheng Zhou; Lingfei Hu; Kai Mu; Zhe Yin (BMC Microbiology)
Abstract The emergence of multidrug-resistant (MDR) Raoultella isolates is linked to the acquisition of antibiotic resistance genes (ARGs) with plasmids playing a pivotal role in this process. While plasmid-mediated transmission of ARGs in Raoultella has been extensively reported, limited attention has been given to genetically dissecting the modular structures of plasmids. This study aims to elucidate the genomic features of novel incompatible plasmids in MDR Raoultella by presenting 13 complete plasmid sequences from four isolates, along with an analysis of 16 related plasmids from GenBank. These 29 plasmids were classified into five distinct groups: IncFII single-replicon plasmids, dual-replicon plasmids containing the IncFII replicon, IncHI plasmids, IncR plasmids, and IncX8 plasmids. A new incompatible group, IncFIIp23141−CTXM, was identified, alongside five newly designated Inc groups based on previously determined sequences, namely IncFIIpKPC2_EC14653, IncFIIpCP020359, IncFIIpCP024509, IncFIIpKOX−137, and IncFIIpKDO1. Furthermore, this research marks the first report of four Inc groups of plasmids within Raoultella, namely IncFIIp23141−CTXM plasmid, IncFIIpKPC2_EC14653 plasmid, IncX8 plasmid, and IncFIIpCP020359: IncFIB-7.1 dual-replicon plasmid. Moreover, novel mobile genetic elements, including two unit transposons (Tn6806 and Tn6891), one IS-based transposition unit (Tn6561), and four insertion sequences (ISRor6, ISRor7, ISRor8, and ISRor9) were discovered. Notably, this is the first report of mcr-9 in clinical Raoultella strains. At least 49 ARGs conferring resistance against 11 different categories of antimicrobials were identified on these 13 plasmids. Overall, this research deepens the understanding of incompatible plasmids in Raoultella, serving as a reference for exploring antibiotic resistance profiles and plasmid diversity in MDR Raoultella.